Effect of Traditional Chinese Medicine nursing on functional rehabilitation and postoperative complications in patients undergoing percutaneous transforaminal endoscopic surgery for lumbar disc herniation (中医护理干预对腰椎间盘突出症行椎间孔镜治疗患者功能康复和并发症的影响) - XU Li (徐丽) (中西医结合护理)
Objective To evaluate the application of Traditional Chinese Medicine nursing on functional rehabilitation and postoperative complications in patients undergoing percutaneous transforaminal endoscopic technique for lumbar disc herniation (LDH). Methods Totally 84 LDH patients undergoing percutaneous transforaminal endoscopic surgery were randomly divided into the control group and observation group, with 42 cases in each group. All patients received routing nursing measures during operation period, and those in the observation group were given Traditional Chinese Medicine nursing techniques for postoperative functional recovery. The Oswestry Disability Index (ODI), Visual Anlogue Scale (VAS) and Japanese Orthopaedic Association scores (JOA) were used to evaluate the postoperative function recovery. The rehabilitation efficacy and incidence of postoperative complications such as disc space infection, deep venous thrombosis of lower extremity and urinary tract infection were compared between two groups. Results The ODI and VAS scores in the observation group were lower than those in the control group(P＜0. 05), and JOA score in the observation group was higher than those in the control group(P＜0. 05). The total effective rate was 95. 24(40/42) in the observation group, which was higher than 78. 57%(33/42) in the control group(P＜0. 05)。The incidence of postoperative complication in the observation group was lower than that in the control group, with a significant difference(P<0. 05). Conclusion The Traditional Chinese Medicine nursing techniques are effective to improve the functional recovery after percutaneous transforaminal endoscopic surgery, and reduce the pain and incidence of postoperative complications. (目的 探讨中医护理干预在腰椎间盘突出症行椎间孔镜治疗患者中的应用效果。方法 将84例行椎间孔镜治疗的腰椎间盘突出症患者随机分为对照组和观察组, 各42例。对照组实施常规护理, 观察组在对照组基础上增加中医护理干预。在术前和术后运用功能障碍指数(ODI)、视觉模拟评分(VAS)、日本骨科协会评估治疗分数(JOA)进行评价, 并比较两组患者疾病康复效果及椎间隙感染、下肢深静脉血栓、泌尿系统感染等并发症发生情况。结果 与对照组比较, 观察组术后ODI、VAS评分降低, JOA评分增加, 差异有统计学意义(P＜0. 05)。观察组总有效率95. 24%(40/42), 高于对照组的78. 57%(33/42), 差异有统计学意义(P＜0. 05)。观察组术后并发症发生率低于对照组, 差异有统计学意义(P<0. 05)。结论 中医护理干预有助于改善腰椎间盘突出症行椎间孔镜治疗患者腰椎功能, 缓解疼痛, 减少并发症发生, 促进康复。)